Identifying the Bargaining Values of a Digital Movement - Muhammad, Ja'far (POLIGOVS, 2023)
The study analyses two cases of digital movements in Indonesia. It identifies who are the actors behind the movement, the spread of the movement, the tactics used to increase exposure, and challenges a digital movement faces. The first case is the movement to reject Firli Bahuri as chairman of the Corruption Eradication Committee (KPK), and the second case is the persecution of David Ozora by Mario Dandy, the son of a tax official. The Firli case represents a long movement that brought a lot of controversies. It attracted massive public attention, shown in the form of, among others viral hashtags on social media, news coverage in mainstream media, and even demonstrations that claimed lives. However, this movement was not successful. On the other hand, the movement that demands the persecution of David Ozora, which only lasted for a few days, successfully moved the government to respond quickly to remove the official’s position, suspect perpetrators, and bring gratuity and money laundering cases into court